Perkembangan Artificial Intelligence: Peluang dan Tantangan Penggunaannya pada Peradilan Konstitusi di Indonesia - Yurisvina Arianto, Ni Kadek Lidya; Suindrayani, Ni Putu Tya (Kertha Patrika; Vol 46 No 2 (2024), 2024)
Technological developments have given birth to a new innovation known as AI. Digitalization and globalization which encourage the use and utilization of AI in judicial institutions by the Constitutional Court is something that needs to be considered, the use of AI can erode the value of human rights. Therefore, this research aims to examine the prospects for using AI related to institutional reform of the Constitutional Court in Indonesia as an effort to achieve and realize justice that is based on simplicity, speed and low costs. This research was conducted using empirical normative research methods. The results of this research show that the Constitutional Court uses AI as an institutional form which refers to efforts to implement the principles of simple, fast and low-cost justice. Implementation Referring to sociological, philosophical and juridical grounds, this is done by issuing legal products in the form of PMK and implemented in the justice administration system by the Constitutional Court Registrar and the Constitutional Court Secretary General.